تحليل العلاقة بين نشاط بورصة الأوراق المالية وأدائها في ظل التقلبات السعرية؛ دراسة حالة بورصة عمان للأوراق المالية - جابو سليم (جامعة الوادي University Of Eloued, 2024)
This studyaims to analyze the relationshipbetween the activity and performance of the Amman Stock Exchange in light of price fluctuations. Given the study's nature and its sensitivity in terms of reflection and dynamic correlation, data were collected through three time intervals during the year 2022. Multiple statistical models were estimated using statistical and technical methods to analyze the data and uncover the reasons behind the impact of price fluctuations on the exchange's performance, utilizing the Smart PLS4 software. The study found that price fluctuations are not correlated over time and have a synchronous effect on returns. Additionally, they do not influence the behavior of investors in the Amman Stock Exchange, as investors do not consider these fluctuations as a factor in their investment decisions. Furthermore, the study concluded that the impact of the Amman Stock Exchange's activity on its returns varies depending on the behavior of investors.
Analysis of the relationship between the activity and performance of the stock exchange in light of price fluctuations A case study of the Amman Stock Exchange
Keywords: تقلبات الأسعار; حجم التداول; معدل العائد; بورصة عمان للأوراق المالية; price fluctuations; trading volume; Total Return Index (ASETR); Amman Stock Exchange